Implementing School–University Partnerships through the Teaching Assistantship Program in Elementary Schools: A Phenomenological Study of PGSD UNM Students - Afdhal Fatawuri Syamsuddin; Muhammad Irfan; Erma Suryani Sahabuddin (Publikasi Pendidikan, 2026)
The Teaching Assistantship in Elementary Schools (AMSD) program represents a strategic effort to strengthen school–university partnerships in preparing prospective primary school teachers. This study investigates how PGSD UNM students meaningfully interpret their AMSD experiences, and how the program contributes to the formation of pedagogical competence and professional identity. Employing a qualitative design with an Interpretative Phenomenological Analysis (IPA) approach, data were collected through in-depth interviews with two PGSD UNM students who had completed the program. Analysis proceeded through initial noting, emergent theme identification, and superordinate theme construction. Five superordinate themes emerged: (1) initial adaptation amid uncertainty; (2) the mentor teacher relationship as a primary learning source; (3) theory–practice integration in the real classroom; (4) the development of teaching competence and professional identity; and (5) personal transformation through field challenges. The findings underscore that AMSD is an effective yet context-dependent transformative experience whose success relies heavily on institutional coordination quality, mentor teacher readiness, and the relational dynamics students navigate in school settings. Recommendations are provided to strengthen AMSD implementation and school–university partnership models.